Cubital tunnel syndrome: A retrospective analysis of surgical management - Shrestha, Prabin; Dhungana, Isha; Kolakshyapati, Manish (Nepal Journal of Neuroscience, 2023)
Introduction: Cubital tunnel syndrome (CuTS) is a condition of ulnar nerve dysfunction due to prolonged compression at the elbow often caused by cubitus valgus deformity of lateral epicondyle fracture. The main objective of this study is to share our experience of and to review the role of surgical decompression and anterior transposition (SDAT) of ulnar nerve in long-term relief of the symptoms.Materials and Methods: Retrieval of case records of CuTS and retrograde analysis of data was performed. The inclusion criteria were availability of relevant clinical information, finding of severe nerve compression in nerve conduction study (NCS), insignificant MRI of cervical spine and SDAT. About 100 cases of ulnar nerve compression underwent surgical management from 2008 till 2021. Of them, only 54 fulfilled all the criteria. Minimum follow up period was 18 months after surgery.Results: Among 54 cases, 20 were females, 34 males, and mean age was 31 years. Three most common clinical features were paresthesia, motor weakness and hand muscle atrophy. Symptomatic relief was achieved in 54/54 (100%) and complete motor recovery in 34/54 (63%) cases after SDAT. However, muscle atrophy recovery was not observed in any. There was no surgical complication, no features of recurrence nor was there re-surgery in any at least for 18 months after surgery.Conclusions: SDAT provides long-term relief for CuTS without recurrence. Muscle atrophy is irreversible though other symptoms improve. Therefore, early surgery before appearance of muscle atrophy is advocated.